Chemistry Concepts in The Process of Making Coconut Oil: A Chemistry Magazine for Senior High School - Rahmawati Rahmawati; Lilik Khaerun Nisa; Lalu Rudyat Telly Savalas; Fara Dwirani Sofia; Syarifa Wahidah Al Idrus; Muti’ah Muti’ah; Sunniarti Ariani; Sya’ban Putra Adiguna (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to identify the chemical concepts contained in the process of making coconut oil, then the results of the identification and documentation are compiled into a chemistry magazine for senior high schools. The process of making coconut oil is done by two methods, namely heating/traditional and fermentation. The preparation of a chemical magazine is carried out using the method according to Borg & Gall which is simplified into five stages, namely preliminary studies, planning, initial product development, field implementation tests, and product finalization. There are several chemical concepts related to the process of making coconut oil, namely macromolecules, mixture separation, boiling point elevation, and colloids. Magazine feasibility testing is done by validating and analyzing student responses. The results showed that the magazine developed was very valid with an average value of V on the components of graphics, content feasibility, presentation feasibility, and magazine language respectively 0.92, 0.91, 0.96, and 0.88. The results of the student response analysis show that the developed magazine is very feasible with an average percentage of 90%.